Analysis of Medical Waste Management Compliance in Health Facilities in Indonesia - Lelyana, Nora (Universitas Mandala Waluya, 2024)
Medical waste management in healthcare facilities is a critical issue in Indonesia due to its significant impact on public health and the environment. This study evaluates medical waste management practices and compliance levels by analyzing secondary data, including government reports, academic studies, and policy documents. The research method used was qualitative, utilizing secondary data, including peer-reviewed articles from databases such as ScienceDirect, PubMed, and Scopus, as well as relevant government and non-governmental organization (NGO) reports. The analysis resulted in three main findings: (1) Medical Waste Management Practices: mapping the actual condition of medical waste management in healthcare facilities; (2) Policy and Implementation Gaps, indicating a lack of regulatory oversight and enforcement; and (3) Diverse Operational Challenges: covering limited institutional capacity, staff training, resources, and awareness of the importance of medical waste management. Multifaceted strategies, including strengthening the regulatory framework, improving staff education and training, and allocating adequate resources, are recommended to address these challenges. This study offers concrete recommendations to improve the effectiveness of medical waste management in health facilities in Indonesia.